Performing an ethos of a dominant Black woman in Paris through body and language: passing at the intersection of race, gender, and class. (1st September 2022) - Telep, Suzie
Abstract : This article aims to illuminate the social meanings of passing experiences through the practice of whitization (or whitening, i.e. speaking and behaving like a White person) among upper-class African Black women in postcolonial France at the intersection of race, gender, and class. I analyze the role of body and language in the process of political emancipation in a Cameroonian female activist, who is a consultant in the field of African fashion and luxury in Paris. After defining whitization as a form of passing, the article analyzes the phonetic and bodily markers of whitening processes among the Black female subject in three interactions in front of different audiences. I show how multiple semiotic forms are used by the doubly minoritized subject to perform simultaneously a dominant Black woman ethos and a cosmopolitan Black beauty, which partially conforms to Western canons of beauty so as to subvert race, gender, and class power structures.